PRONOMINA DEMOSTRATIF BAHASA JAWA DALAM MAJALAH DJAKA LODANG - Wahyu Widiyawati; Nusarini Nusarini (CARAKA, 2019)
This study aims to describe (1) the types of Javanese language demonstrative pronouns in Djaka Lodang magazine, (2) references to the Javanese language demonstrative pronouns in Djaka Lodang magazine, and (3) syntactic function to the Javanese language demonstrative pronouns in Djaka Lodang magazine. This study included a type of qualitative descriptive research. The data in this study are in the form of sentences and paragraphs containing Javanese language demonstrative pronouns. The data source of this study is in the form of Djaka Lodang magazine from March to April 2018. The method of providing data, namely by referring to the method includes the technique of referring to skillful involvement and note-taking techniques. The method of data analysis is the agih method with the basic techniques for direct elements and advanced techniques, namely the sloping technique, expanded techniques, and sentence constituent analysis techniques. The method of presenting the results of data analysis is done by informal methods. The results of the research on the Javanese language demonstrative pronouncement in Djaka Lodang magazine are as follows. (1) The types of Javanese language demonstrative pronouns in Djaka Lodang magazine have five namely substantive demonstrative pronouns, locative demonstrative pronouns, descriptive demonstrative pronouns/modalities, temporal demonstrative pronouns, and demonstrative pronouns of directions. (2) There are two references to the Javanese language demonstrative pronoun in the Djaka Lodang magazine, namely the reference of endospores and references to exophora. (3) There are three syntactic functions of the Javanese demonstrative pronouncement in Djaka Lodang magazine, namely the subject function, the predicate function, and the information function.